PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA SD - SURYANA RAJAGUKGUK (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2023)
In the teaching and learning process, various types of learning models can be used. One of the learning models is Project based learning. This model is usually often used in teaching in elementary schools. The learning process only guides student learning outcomes. Moreover, the teacher assesses the suitability of what is conveyed, not to think creatively about the product so that the product is effective in learning. By using the Project based learning learning model that starts from basic questions, organizing, scheduling, monitoring, presenting and evaluating projects can increase student creativity or student creative thinking. The created problem is then made into a product in progress. The purpose of this research is to find out the application of Project based learning to increase the creativity of elementary school students. This writing uses literature research to analyze 10 journals that match the title raised. The data used is secondary data, namely data obtained indirectly from previous research. Data collection techniques by analyzing books, theses and classroom action research journals related to increasing creativity by using the Project based learning learning model. The method used is a qualitative research method. From the results of the journals that have been analyzed, it can be said that not only learning outcomes have increased but children's creativity has also increased. ABSTRAKDalam proses belajar mengajar, berbagai jenis model pembelajaran yang dapat digunakan. Salah satu model pembelajaran yaitu Project based learning. Model ini biasanya sering digunakan dalam mengajar di SD. Adapun proses pembelajaran hanya menuntun hasil belajar siswa. Apalagi guru lebih menilai kesesuaian dengan yang disampaikan bukan kepada berpikir kreatif terhadap produk sehingga produk tepat guna dalam pembelajaran. Dengan menggunakan model pembelajaran Project based learning yang dimulai dari pertanyaan mendasar, mengorganisasi, membuat jadwal, memonitoring, menyajikan dan mengevaluasi proyek dapat meningkatkan kretivitas siswa atau berpikir kreatif siswa. Masalah yang dibuat kemudian dijadikan suatu produk dalam penyelesaian. Tujuan penelitian ini hendak mengetahui penerapan Project based learning untuk meningkatkan kreativitas siswa SD. Penulisan ini menggunakan penelitian literatur menganalisis 10 jurnal yang sesuai dengan judul yang diangkat. Adapun data yang digunakan adalah data sekunder yaitu data yang diperoleh secara tidak langsung dari penelitian terdahulu. Teknik pengumpulan data dengan menganalisis buku, skripsi dan jurnal penelitian tindakan kelas yang berhubungan meningkatkan kreativitas dengan menggunakan model pembelajaran Project based learning. Metode yang digunakan adalah metode penelitian kualitatif. Dari hasil jurnal yang sudah dianalisis maka dapat dikatakan bukan hanya hasil belajar yang meningkat tetapi kerativitas anak juga meningkat.